2023
DOI: 10.3389/fmed.2023.1091634
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension, type 2 diabetes, obesity, and p53 mutations negatively correlate with metastatic colorectal cancer patients’ survival

Abstract: IntroductionWe studied the predictive and prognostic influences of hypertension (HT), type 2 diabetes (T2D), weight, and p53 mutations in metastatic colorectal cancer (CRC) patients.Patients and methodsT2D was diagnosed according to the ADA criteria. HT was classified according to the ACC/AHA guidelines. BMI (body-mass index) was calculated and classified according to the WHO criteria. TruSigt™Oncology 500 kit was applied to construct the genomic libraries for Next Generation Sequencing (NGS) analysis. The Ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
(61 reference statements)
0
0
0
Order By: Relevance
“…One study showed that MutP53 protein expression is positively correlated with tumor diameter (29). Another study showed that patients with high MutP53 proteins expression have a significantly shorter survival time than patients with high expression of the wild-type P53 protein (30). Moreover, patients with CRC with dMMR have significantly lower MutP53 proteins expression than patients with pMMR (31).…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that MutP53 protein expression is positively correlated with tumor diameter (29). Another study showed that patients with high MutP53 proteins expression have a significantly shorter survival time than patients with high expression of the wild-type P53 protein (30). Moreover, patients with CRC with dMMR have significantly lower MutP53 proteins expression than patients with pMMR (31).…”
Section: Discussionmentioning
confidence: 99%
“…The database search yielded 802 studies for screening (PubMed (n = 425), Embase (n = 124), Web sciences (n = 107), Scopus (n = 87), Cochrane Library (n = 34), CINAHL (n = 25)), of which 298 abstracts were identified as potentially eligible and retrieved for full-text review. Finally, 16 articles met the eligibility criteria and were included in this systematic review and meta-analysis [3,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. The detailed PRISMA flowchart for study screening and selection is presented in Figure 1.…”
Section: Identification Of Studiesmentioning
confidence: 99%
“…All the included articles were published between 2009 and 2023 and originated from eight countries. Among the 16 articles included in this systematic review and meta-analysis, 15 were retrospective [3,[17][18][19][20][21][22][24][25][26][27][28][29][30][31], and only 1 was a prospective study [23]. The sample size of the included articles varied from 45 to 750 participants, with a slightly higher proportion of male patients (58%).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Clinical outcomes, however, can differ significantly between patients with resectable diseases. Tumor symptoms encompass several factors such as type 2 diabetes, nutritional deficiencies, diabetes, obesity, and smoking, which have been found to be associated with reduced odds of survival [3,4]. CRC typically recurs in 60 to 80% of cases and 95% within four years of resection [4,5].…”
Section: -Introductionmentioning
confidence: 99%
“…Tumor symptoms encompass several factors such as type 2 diabetes, nutritional deficiencies, diabetes, obesity, and smoking, which have been found to be associated with reduced odds of survival [3,4]. CRC typically recurs in 60 to 80% of cases and 95% within four years of resection [4,5]. Colon malignancies are frequently identified by the utilization of needle biopsy or fine needle aspiration (FNA) techniques [5,6].…”
Section: -Introductionmentioning
confidence: 99%